The "Intimidating" Archives: Teaching Graduate Students Historical Research Methods. Issue 3 (September 2017) - Note, Margot
This article discusses approaches I used to teach "Research Methods, " an archival-based course for a history graduate program at a small college. The instruction included baseline research strategies for students new to the humanities as well as advanced methodologies for experienced researchers, with attention given to archival research techniques. Most professional literature focuses on teaching archival literacy aimed at K-12 students or undergraduates; this article explores the distinct research and instruction needs of graduate students. It examines how graduate students perceive the research process, what difficulties they encounter while conducting research, and what impact attending the course could have on their long-term research procedures. While teaching the course, I discovered that students viewed archives as intimidating. By acknowledging that new users can feel daunted by researching archival collections, instructors and archivists can consider how to make the archives more welcoming to first-time visitors.